The structure of second Corinthians : Paul's theology of ministry - Kei, Hiramatsu, autor (Library of New Testament studies, 2023)
Hiramatsu Kei examines the literary structure of 2 Corinthians and how it can illuminate understanding of this Pauline letter and its theological message. He explores the theoretical foundations of Inductive Bible Study as an approach, which focuses on the meaning of biblical texts in their final form by incorporating insights from multifarious methodologies. Based on the final form of the letter and its compositional unity, he prioritizes the literary context as consequential evidence for interpretation.